A dollar for Penny - Glass, Julie; Allen, Joy (New York : Random House, 2000)
Penny sets up a lemonade stand to earn money for her mother's birthday card and learns about currency.
F
410
F
Keywords: Money -- Fiction; Moneymaking projects -- Fiction; Birthdays -- Fiction; Stories in rhyme